Molecular structure stability of short-chain chlorinated paraffins (SCCPs): Evidence from lattice compatibility and Simha-Somcynsky theories - YUMAK YAHŞİ, AYŞE; YAHŞİ, UĞUR (ELSEVIER SCIENCE BV, 2015)
In is known that short-chain chlorinated paraffins (SCCPs) are highly complex technical mixtures of polychlorinated n-alkanes with single chlorine content. Due to their physical properties (viscosity, flame resistance) they are used in many different applications, such as lubricant additives, metal processing, leather fat-liquoring, plastics softening, PVC plasticizing and flame retardants in paints, adhesives and sealants. SCCPs are studied here in terms of processing-linked molecular structure stability, under Simha and Somcynsky-EOS theory calculations and elements from Simha-Somcynsky-related Lattice Compatibility Theory. Analyses were carried out on 1-chloropropane, 2-chloropropane, 1-chlorobutane, 2-chlorobutane, 1-chloro 2-methylane, and 2-chloro 2-methylane as (SCCPs) universal representatives. This paper gives evidence to this stability and reviews the current state of knowledge and highlights the need for further research in order to improve future (SCCPs) monitoring efforts. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Short-chain chlorinated paraffins; LCT; Simha-Somcynsky theory; Free volume; Hole fraction; Thermo-occupancy function; PHASE-TRANSITION; BINARY-MIXTURES; THEORY LCT; PATTERNS; PURE; DEGRADATION; TEMPERATURE; CRYSTALS; DYNAMICS